O que a arquitetura mascara? : uma arqueologia da compartimentação, da vigilância e dos aspectos de concessão e restrição à circulação no Solar dos Ferreiras, Campanha/MG (século XIX) - Leonardo Lopes Villaça Klink (2023)
How and in what ways does architecture composed of ornamentation, walls, corridors, doors and windows affect behaviors, experiences and choices in circulations? As a vector research object to these questions, I analyze the ruins of Solar dos Ferreiras, remnants of a mansion built in the 19th century in Campanha, – southern region of Minas Gerais –, by a family of considerable prominence and social, political and economic projection, as well as extensive networks of sociability in the Rio de Janeiro Court. Starting from the perspective of total institutions and an integral archaeological analysis between the documentary and architectural remains, I propose initially to verify the numerous metamorphoses of its spatial configuration, in order to partially “reach” the plans of the structure closer to what it may have been during its first generation of occupants, which I also recover and “(re)construct” through biographical narratives. Based on methods derived from the Theory of Space Syntax in the development of the research and in the elaboration of a methodological tool that I called “degree of axial dispersion”, I’m interested in discussing how different spaces and places that make up the different spheres of this social unit would refer to changes in behavior, discourses of power, experiences of coexistence and a domestication of the systems of encounters, principles of segregation and incorporation between and about free and enslaved residents. Groups of people that are socially and culturally distant, but linked by the intrinsic everyday relationships.